COMPARISON OF FOUR DIFFERENT ENDODONTIC ROTARY SYSTEMS IN TERMS OF CYCLIC FATIGUE - Tolga Ceyhanlı; Ahter Şanal Çıkman (Cumhuriyet University, 2022)
Objectives: The aim of this study was to compare four endodontic rotary systems in terms of cyclic fatigue. Material and Methods: 25/.08 Twisted File (TF), TF Adaptive, Reciproc and WaveOne rotary files were used to test the cyclic fatigue strength in this study. Four different artificial canals, compatible with the file size and taper, were created, with the curvature angle and radius of 450-2 mm, 600-2 mm, 450-5 mm and 600-5 mm, respectively. The front surface of the artificial canals was covered with a removable glass plate. The files were operated in the canals according to their own working principles until they fractured. The fracture time was determined by using a chronometer with 1/100 second accuracy and the cyclic fatigue strength was evaluated according to the time until fracture occurs. A total of 40 files, 10 in each canal, were used in each group. SPSS program was used for statistical analysis. Mann-Whitney U test was applied for pairwise comparisons. Bonferroni correction was applied and P<0.008 was considered as statistically significant. Results: In all canals, fracture time was the highest for Reciproc files, followed by WaveOne, TF Adaptive and TF files, respectively. For the canal curvature of 450-2 mm, the Reciproc files were significantly more resistant to fracture than the others. While there was no significant difference between TF Adaptive and TF, WaveOne was significantly more resistant than both groups. In canals with the curvature of 600-2 mm and 450-5 mm Reciproc and WaveOne were significantly more resistant to fracture than TF Adaptive and TF. In addition, TF Adaptive was significantly more resistant than TF. For the curvature of 600-5 mm, the difference between all groups was significant. Conclusions: Regardless of the canal curvature, the Reciproc exhibited the highest cyclic fatigue strength, while the TF showed the lowest fatigue strength.